Determination of Biological Activity of Hylocereus polyrhizus Methanol Extracts: Antimicrobial Activity, Probiotic-Promoting Effect, Photoprotective Activity - Celik, Irem; Saglam, Ali; Asan-Ozusaglam, Meltem (International Journal on Food, Agriculture and Natural Resources, 2024)
In our study, the biological activity of Hylocereus polyrhizus obtained from Türkiye was determined. Firstly, antimicrobial activity of methanol extracts obtained from H. polyrhizus against test microorganisms was determined by disc diffusion susceptibility assay, minimum inhibition concentration (MIC) and minimum fungicidal or bactericidal concentration (MFC or MBC) tests. Then, viable cell counting against Limosilactobacillus fermentum MA-7 using the macro-dilution method was used to determine the probiotic-promoting effect of the fruit extracts. Finally, the photo-protective activity of the extracts and extract-cream mixtures was obtained spectrophotometrically. The inhibition zone diameter of the peel extract against the test microorganisms is in the range of 9.60-12.37 mm and the fruit extract is in the range of 7.85-12.00 mm. MBC values ranged from 40 µg/µl to 80 µg/µl in peel extract and between 10 µg/µl and >80 µg/µl in the fruit extract. The inhibition zone diameters of the extracts against probiotics were determined as 6.10 -10.25 mm. As a result of the viable cell count, the viability rate of L. fermentum MA-7 increased as the fruit methanol extract concentration and time increased. The photoprotective activities of the peel and fruit extracts were determined as 13.17 and 12.26. It was determined that the extracts increased sun protection factor (SPF) value of the cream. The results indicated that H. polyrhizus extracts may have potential for use in the nutraceutical products, cosmetic and pharmaceutical industries.